Code of criminal procedure,1973 (Act No II of 1974) - Vakil, Manharlal Ratanlal (ed.); Ratanlal; Dhirajlal (Nagpur, 1984)
This book is about the code of criminal procedure, 1973.
Keywords: Criminal procedure